Engineering thermophilic Geobacillus thermoglucosidasius for riboflavin production. Issue 2 (25th February 2020) - Yang, Zhiheng; Sun, Qingqing; Tan, Gaoyi; Zhang, Quanwei; Wang, Zhengduo; Li, Chuan; Qi, Fengxian; Wang, Weishan; Zhang, Lixin; Li, Zilong
Summary: The potential advantages for fermentation production of chemicals at high temperatures are attractive, such as promoting the rate of biochemical reactions, reducing the risk of contamination and the energy consumption for fermenter cooling. In this work, we de novo engineered the thermophile Geobacillus thermoglucosidasius to produce riboflavin, since this bacterium can ferment diverse carbohydrates at an optimal temperature of 60°C with a high growth rate. We first introduced a heterogeneous riboflavin biosynthetic gene cluster and enabled the strain to produce detectable riboflavin (28.7 mg l −1 ). Then, with the aid of an improved gene replacement method, we preformed metabolic engineering in this strain, including replacement of ribC Gtg with a mutant allele to weaken the consumption of riboflavin, manipulation of purine pathway to enhance precursor supply, deletion of ccpN Gtg to tune central carbon catabolism towards riboflavin production and elimination of the lactate dehydrogenase gene to block the dominating product lactic acid. Finally, the engineered strain could produce riboflavin with the titre of 1034.5 mg l −1 after 12‐h fermentation in a mineral salt medium, indicating G. thermoglucosidasius is a promising host to develop high‐temperature cell factory of riboflavin production. This is the first demonstration of riboflavin production in thermophilic bacteria at an elevated temperature. Abstract : Taking advantage of Geobacillus thermoglucosidasius with the characteristics of fast growth and utilization of diverse inexpensive substrates, here we demonstrated that this strain could be used as a promising alternative host for biosynthesis of riboflavin. Afterward, a sequential of engineering strategy was applied to improve riboflavin titers in the G. thermoglucosidasius producer to 1034.5 mg l −1 at 12‐h flask fermentation in a simple mineral salt medium. As proof‐of‐concept, our work presented the feasibility of riboflavin production by engineering the thermophilic G. thermoglucosidasius . More importantly, the present work paves the way to further systematic metabolic engineer this thermophilic host for riboflavin production.